1997
DOI: 10.1021/bk-1997-0662.ch008
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosides of Sucrose in Foods: Composition, Flatulence-Causing Effects, and Removal

Abstract: Alpha-galactosides of sucrose, namely raffinose, stachyose and verbascose, are widely distributed in higher plants, especially leguminous seeds. In addition the presence of galactopinitol, galactinol, mannitriose and melibiose in Brassica campestris, soybean and some legumes has been reported. Due to the absence of a -galactosidase activity in human and animal intestine mucosa, these oligosaccharides escape digestion and they are metabolized by bacteria to hydrogen, carbon dioxide and methane. Thus, they are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…One of the aspects studied in different species is the mobilization of reserve compounds during seed germination. Non-germinated canola seed contain about 0.4 g lipid g cotyledons -1 (Nykiforuk and Johnson-Flanagan, 1994) and 0.08 g of soluble carbohydrate g cotyledons -1 (Naczk et al 1997). Carbohydrates and lipids in cotyledons are metabolized during seed germination and their products are used in root and seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…One of the aspects studied in different species is the mobilization of reserve compounds during seed germination. Non-germinated canola seed contain about 0.4 g lipid g cotyledons -1 (Nykiforuk and Johnson-Flanagan, 1994) and 0.08 g of soluble carbohydrate g cotyledons -1 (Naczk et al 1997). Carbohydrates and lipids in cotyledons are metabolized during seed germination and their products are used in root and seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition soybean seeds contain verbascose (Karr-Lilienthal et al 2005). Some of these carbohydrates are non-digestible and have been shown to be associated with abdominal distension and flatulence in humans (Naczk et al 1997;Sarkar et al 1997a). During fermentation microorganisms hydrolyze non-digestible carbohydrates into sugars which are readily digestible by humans and in addition positively influence the texture of the product by softening the tissue (Odunfa 1983;Ouoba et al 2007a;Sarkar et al 1997a).…”
Section: Carbohydratesmentioning
confidence: 99%
“…Thus, to identify new SNPs in the mutant population, an empirically determined frequency of polymorphism from our spike-in control was used as a starting point. After calling SNPs that appeared in the sequenced DNA, we prioritized screening SNPs that met two criteria: (1) An occurrence above a cutoff of 0.15% (above the noise level but somewhat lower than the expected frequency for a homozygous mutation); (2) that created non-synonymous substitutions or nonsense mutations at a conserved position and were, therefore, predicted to be damaging for protein function. We preferred to select SNPs that resulted in a G to A or C to T change diagnostic of NMU-induced mutation (and less likely to be PCR error), and that was unique to one library (thus not a result of amplification of sequences from a homologous sequence in the soybean genome).…”
Section: Sequencing Of Rs2 and Rs3 Ampliconsmentioning
confidence: 99%
“…However, the soybean seed also contains carbohydrates that are considered antinutritional. Raffinose and stachyose family oligosaccharides (RFOs) are not easily digested by monogastric animals [2,3], and studies have suggested that lower levels of raffinose and stachyose contribute to faster livestock growth and to better overall health [4,5].…”
Section: Introductionmentioning
confidence: 99%